Perdagangan luar Malaysia dalam konteks AFTA, NAFTA dan EU: pendekatan model graviti - Sahlan, Rizaudin; Abdullah, Muhammad Ridhuan Bos (Universiti Utara Malaysia, 2007)
The objective of this paper is to examine the factors influencing Malaysian trade with the AFTA, EU, and NAFTA. To determine this trading relationship,the work performed was based on the gravity model estimation introduced by Timbergen (1962). The other variables that included in this analysis which are the determinants of the flow of trade, are the Gross National Product(GNP) for Malaysia and trading partners, distance between two countries, population, and the economic groups, namely NAFTA, EU, and AFTA. The results showed that the volume of trade, GNP, and population is stationarity in first differences with the LCC panel unit root test version. The cointegration test showed that the gravity model used was cointegrating, which means there is long-run relationship among the variables. Furthermore, the estimation of the gravity model with the panel ECM version showed that the GNP and population for Malaysia and trading partners, distance, and the role of economic groups like NAFTA and EU, was significant for determining the relationship of Malaysia’s trade flow with the trading partners.